Measurement of Health, the Sensitivity of the Concentration Index, and Reporting Heterogeneity - Nicolas R. Ziebarth (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Using representative survey data from the German Socio-Economic Panel Study (SOEP) for 2006, we show that the magnitude of such health inequality measures as the concentration index (CI) depends crucially on the underlying health measure. The highest degree of inequality is found when dichotomized subjective health measures like health satisfaction or self-assessed health (SAH) are employed. Measures of medical care usage like doctor visits result in substantially lower concentration indices. Moreover, with the use of SF12, a generic health measure, the inequality indicator is reduced by a factor of ten. Scaling SAH by means of the SF12 leads to similar results to those with the pure SF12 measure. Employing generic health measures used with other populations like the Canadian HUI-III or the Finish 15D to cardinalize SAH has a significant impact on the degree of inequality measured. Finally, by contrasting the physical health component of the SF12 to the unambiguously objective grip strength measure, we provide evidence of the presence of income-related reporting heterogeneity in generic health measures.
Keywords: D30; D31; D63; I10; I12; 330; Health measures; health inequality; SF12; grip strength; SOEP